Do differences among accelerators explain differences in the performance of member ventures? Evidence from 117 accelerators in 22 countries - Chan, Chien Sheng Richard; Patel, Pankaj C.; Phan, Phillip H. (Strategic Entrepreneurship Journal, 2020)
Abstract Research Summary Whether differences among accelerators explain differences in the performance of member ventures is an important and underexplored question. Conversely, are the effects of accelerators so isomorphic, because they copy each other, that ventures from different accelerators report little performance differences? We use variance decomposition analysis to test whether variations in characteristics of accelerators explain performance differences in the ventures that belong to them. Using a sample of 1,442 ventures from 117 accelerator programs across 22 countries, we find that 11.13–14.18% variance of venture performance can be attributed to accelerator membership. Accelerator membership also accounted for 3.00, 5.15, and 16.65% in the variance for employee growth, employee costs, and revenue change, respectively. Our findings suggest that between accelerator differences can make a significant economic difference to venture performance. Managerial summary For accelerator managers and policymakers assessing if differences between accelerators explain the differences in outcomes of member ventures is important. This article advances our understanding of differences among accelerators driving differences in performance among their ventures. Using a sample of 1,442 ventures from 117 accelerator programs across 22 countries, about 11% variance of venture performance can be attributed to accelerator membership. Overall, differences among accelerators seem to explain meaningful differences in performance among member ventures.